Effects of meteorological variables and holidays on the concentrations of PM10, PM2.5, O3, NO2, SO2, and CO in Tehran (2014-2018) - Mostafa Hadei (Journal of Air Pollution and Health, 2019)
Introduction: The aim of this study was to investigate the concentrations of PM10, PM2.5, O3, NO2, SO2, and CO in Tehran during March 2014-March 2018, and evaluate the effects of holidays and meteorological parameters on the air pollution levels. Materials and methods: Hourly concentrations of PM10, PM2.5, O3, NO2, SO2, and CO in different air quality monitors of Tehran were acquired. The data from each air quality monitored were validated, and only high-quality monitors were included in this study. Results: The 4-year averages of PM10, PM2.5, O3, NO2, SO2, and CO concentrations were 88.74 (μg/m3), 31.02 (μg/m3), 34.87 (ppb), 71.01 (ppb), 20.04 (ppb), and 3.78 (ppm), respectively. Higher concentrations of PM10 and O3 were observed during summer. In case of PM2.5 and CO, autumn and winter concentrations were higher than those in springer and summer. Lower concentrations of PM10 and NO2 in Fridays were observed comparing to other days of week. Ozone had high concentrations in Fridays as the weekend in Iran. Except for O3, all of the pollutants had higher concentrations in the working days, comparing to those in any type of vacation days. Concentrations of all pollutants rather that SO2 and O3 in Nowruz holidays were statistically lower than those in the working days. By controlling for the effects of meteorological variables, our results showed that the air pollution control policies and actions have been not effective for particulate matter. Conclusion: These results determines the time periods in which the concentrations of criteria air pollutants are high. This can be very useful for announcing alarms for citizens, and designing the air pollution control plans. In addition, more effective actions should be designed and implemented for reducing ambient levels of particulate matter.